Psychosocial interventions for responding to child sexual abuse: A systematic review. (June 2021) - McTavish, Jill R.; Santesso, Nancy; Amin, Avni; Reijnders, Megin; Ali, Muhammad Usman; Fitzpatrick-Lewis, Donna; MacMillan, Harriet L.
Abstract: Background: In this manuscript, we summarize the findings of a systematic review that informed the development of the World Health Organization's recommendations related to psychosocial interventions for child and adolescent sexual abuse. Method: Systematic searches across 14 databases were conducted to retrieve any published randomized controlled trials of psychosocial interventions addressing mental health outcomes among children and adolescents exposed to sexual abuse who have experienced symptoms. We assessed study risk of bias using the Cochrane Risk of Bias tool and certainty of the evidence using GRADE (Grading of Recommendations Assessment, Development and Evaluation) criteria. Results: Twenty-four articles representing fifteen studies were included in the systematic review. Only two studies were conducted in low- or middle-income countries. Few studies could be pooled together because of differences in interventions and comparators. Due to the small numbers of participants and very serious concerns with risk of bias, we are very uncertain about the benefits of interventions provided to children alone and without the involvement of their caregivers. However, cognitive behavior therapy (CBT) with a trauma focus provided to children and involving their caregivers may reduce some mental health symptoms associated with sexual abuse experiences. Discussion: The findings suggest that more and larger studies are needed to evaluate the effects of psychosocial interventions for children and adolescents exposed to sexual abuse who preside in low- and middle-income countries. PROSPERO registration number: CRD42016039656